2019
DOI: 10.1021/acs.jpca.8b11809
|View full text |Cite
|
Sign up to set email alerts
|

Valence-Shell Photoionization of C4H5: The 2-Butyn-1-yl Radical

Abstract: We present new high-resolution data on the photoionization of the 2-butyn-1-yl radical (CH3CC–•CH2) formed by H atom abstraction from 2-butyne by F atoms. The spectra were recorded from 7.7 to 11 eV by using double-imaging, photoelectron–photoion coincidence spectroscopy, which allows the unambiguous correlation of photoelectron data and the mass of the species. The photoionization spectrum shows significant resonant autoionizing structure converging to excited states of the C4H5 + cation, similar to what is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 46 publications
9
31
1
Order By: Relevance
“…Nevertheless, a weak vibrational component was observed at (11.170 ± 0.002) eV consistent with the PFI-ZEKE value for the first AIE (145). In the case of the OH radical, there have been two measurements of the photoionization cross-section at vuv photon energies, derived from a synchrotron source (146,147). In both cases, cross-sections were measured at photon energies which are above the first AIE but below the second AIE.…”
Section: 4 Andsupporting
confidence: 72%
See 2 more Smart Citations
“…Nevertheless, a weak vibrational component was observed at (11.170 ± 0.002) eV consistent with the PFI-ZEKE value for the first AIE (145). In the case of the OH radical, there have been two measurements of the photoionization cross-section at vuv photon energies, derived from a synchrotron source (146,147). In both cases, cross-sections were measured at photon energies which are above the first AIE but below the second AIE.…”
Section: 4 Andsupporting
confidence: 72%
“…Partial pressures of OH were determined by fitting the observed time traces of the OH + signal, produced by vuv ionization of OH, with a kinetics model constructed using available rate coefficients.Photoionization cross-sections values were reported at 13.435 and 14.193 eV(146). In the second study(147), which is simpler and more direct, OH was produced from the F + H2O reaction, where fluorine atoms were produced by microwave discharge of a flowing F2/He mixture, and the OH absolute cross-section was measured at 13.8 eV. This was achieved by measuring the photon intensities of H2O + , OH + and O + at 13.8 eV with the microwave discharge on and off.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The total energy resolution is in fact a convolution of the electron bandwidth that is used to obtain the TPES and the photon resolution. This issue has been discussed previously 58,59 and we have found that the 50 meV electron bandwidth translates into a resolution of 13 meV. Due to spectral congestion, the width of the peaks in the TPES well exceed the total energy resolution which is the convoluted value of the electron resolution and photon resolution.…”
Section: Methodsmentioning
confidence: 58%
“…Such energy calibrations using higher harmonic ionizations of the contents of the molecular beam have been performed previously and discussed in detail elsewhere. 58,59 In order to correct for possible drifts in the C 60 neutral density, i.e. the relative intensities of the bands between the scans, a ''fast'' scan was performed over the entire energy range with 0.1 eV step sizes with the same acquisition time per point as in the aforementioned scans which had significantly smaller step sizes.…”
Section: Methodsmentioning
confidence: 99%